A 12-month follow-up of the immune response to SARS-CoV-2 primary vaccination: evidence from a real-world study - Fedele, Giorgio; Schiavoni, Ilaria; Trentini, Filippo; Leone, Pasqualina; Olivetta, Eleonora; Fallucca, Alessandra; Fiore, Stefano; Di Martino, Angela; Abrignani, Sergio; Baldo, Vincenzo; Baldovin, Tatjana; Bandera, Alessandra; et al. (Frontiers in Immunology, 2023)
A real-world population-based longitudinal study, aimed at determining the magnitude and duration of immunity induced by different types of vaccines against COVID-19, started in 2021 by enrolling a cohort of 2,497 individuals at time of their first vaccination. The study cohort included both healthy adults aged ≤65 years and elderly subjects aged >65 years with two or more co-morbidities. Here, patterns of anti-SARS-CoV-2 humoral and cell-mediated specific immune response, assessed on 1,182 remaining subjects, at 6 (T6) and 12 months (T12) after the first vaccine dose, are described. At T12 median anti-Spike IgG antibody levels were increased compared to T6. The determinants of increased anti-Spike IgG were the receipt of a third vaccine dose between T6 and T12 and being positive for anti-Nucleocapside IgG at T12, a marker of recent infection, while age had no significant effect. The capacity of T12 sera to neutralize in vitro the ancestral B strain and the Omicron BA.5 variant was assessed in a subgroup of vaccinated subjects. A correlation between anti-S IgG levels and sera neutralizing capacity was identified and higher neutralizing capacity was evident in healthy adults compared to frail elderly subjects and in those who were positive for anti-Nucleocapside IgG at T12. Remarkably, one third of T12 sera from anti-Nucleocapside IgG negative older individuals were unable to neutralize the BA.5 variant strain. Finally, the evaluation of T-cell mediated immunity showed that most analysed subjects, independently from age and comorbidity, displayed Spike-specific responses with a high degree of polyfunctionality, especially in the CD8 compartment. In conclusion, vaccinated subjects had high levels of circulating antibodies against SARS-CoV-2 Spike protein 12 months after the primary vaccination, which increased as compared to T6. The enhancing effect could be attributable to the administration of a third vaccine dose but also to the occurrence of breakthrough infection. Older individuals, especially those who were anti-Nucleocapside IgG negative, displayed an impaired capacity to neutralize the BA.5 variant strain. Spike specific T-cell responses, able to sustain immunity and maintain the ability to fight the infection, were present in most of older and younger subjects assayed at T12.